Prevalence of arterial hypertension among workers in a petrochemical industry (Research, Society and Development, 2024)
Objective: To evaluate the prevalence of systemic arterial hypertension (SAH) among workers in a petrochemical industry. Method: This is a cross-sectional study, carried out between April and June 2023, among 537 workers from a petrochemical industry in the city of Paulinia, state of São Paulo. Data were collected at the participants' own place and working time, from 7:30 am to 10:30 am, blood pressure measurement followed the technique described in the Brazilian Hypertension Guidelines. Results: Participants were between 18 and 63 years old, average 41.6 (±9.2) years old, the majority had completed high school (79.7%) and the research site had a predominance of male workers (96.3%). It was found that 49.1% of the study participants had SAH, among the 20 women, 15% were hypertensive, and among the men, 50.4% had SAH. In the evaluation of the previous diagnosis of hypertension, among hypertensive men, 73.5% reported not having a previous diagnosis of the disease, and in this group, the highest prevalence of hypertension was among those aged 40 to 49 years (37.5%), followed by the group aged 30 to 39 (37.0%). Conclusion: The prevalence of hypertensive patients in this study can be considered an important epidemiological finding, especially when analyzing male workers in isolation. Therefore, a rigorous health intervention, led by the Occupational Nursing team, and with the occupational health and people management teams actively participating, is necessary so that the program's objectives are achieved.